Last exit to Lisbon - Jean Pisani-Ferry; André Sapir (Bruegel, 2006)
Jean Pisani-Ferry and André Sapir call for more focused guidelines in Lisbon 2, an explicit methodology for evaluating National Reform Programmes, and better ownership of these programmes to encourage national debate on key areas of underperformance in member states. This paper, prepared at the request of the Austrian Presidency, was presented to the European Union's finance ministersin Brussels.
Keywords: 330; Strukturwandel; Wirtschaftspolitik; Reform; EU-Staaten; Lissabon Strategie